HAS HIGHER EDUCATION BECOME FEMINE AT THE LEADERSHIP LEVEL? - Borsos, Eszter (Studia Mundi – Economica, 2022)
The aim of my present study is to present the current situation of higher education in terms of leaders, mainly relying on secondary databases. We have known for decades (and many scientists have already written it) that education has become a fundamentally feminized profession in the twentieth century, especially for the 21st century. Of course, the situation resulting from this process had and still has many economic aspects, so the chosen topic is not only the result of a combination of social factors. The question for me is, that the “queen” of education, a career in higher education with the highest prestige values, open for women leaders? If yes, how open are women themselves to this kind of career? Do they appear not only on the faculty and research side, but also in leadership? Were the changes in higher education models affected their status? Of course, due to the limitations of the study, I do not seek to answer these questions in full, but my goal is to provide a comprehensive picture through domestic and a little international perspective.